Islamic Business Ethics Research in Google Scholar Using Bibliometrix Analysis - Sofyan, A Syathir; Arsyad, Ummy Aisyah; Aprilia, Hismayanti; Putri, Nurandini (Darul Yasin Al Sys, 2025)
This research aims to see the development trend of Islamic business ethics studies in the scope of business and management published in Shinta indexed journals. This research uses bibliometric method with R Studio analysis tool which is used to analyse bibliographic data obtained automatically. The results showed that the number of Islamic business ethics publications has increased along with the number of Muslim entrepreneurs who apply Islamic business ethics in their business processes. The results of bibliometric analysis found that Islamic business ethics research is dominated by Islamic business ethic and ethic which uses more quantitative approaches. Furthermore, some research themes that can develop in the future are themes related to Product Quality Issue and Service Quality Issue. This study contributes to future research and provides scientific novelty in the assessment of Islamic business ethics publications in the scope of business and management and is also practically and theoretically very important for academics.